The Influence of PLN Empowered Village Innovation on Capacity HR in Manistutu Village, Jembrana Regency, Bali - I Made Arya; Komang Agus Rudi Indra Laksmana; Wayan Ardani; Ni Luh Ketut Ayu Sudha Sucandrawati (Cita konsultindo, 2026)
This study investigates the impact of the